Late Permian siliceous hot springs developed on the margin of a restricted epeiric sea: Insights into strata-confined silicification in mixed siliciclastic‑carbonate successions - Varejão, Filipe G.; Warren, Lucas V. [UNESP]; Alessandretti, Luciano; Rodrigues, Mariza G. [UNESP]; Ricomini, Claudio; Assine, Mario [UNESP]; Cury, Leonardo F.; Faleiros, Frederico M.; Simões, Marcello Guimarães [UNESP] (Elsevier, 2022)
Hot springs are sources of carbonate minerals in modern settings; however, few fossil structures are recorded in successions older than the Quaternary due to their enhanced erosional potential. >4500 siliceous mounds are recognized in a well-defined level from the upper part of the Permian Teresina Formation (Paraná Basin, SE Brazil). Additionally, a new mound level is here reported for the first time about 15 m below the main occurrence. Remarkable lithological, mineralogical, paleontological and geochemical features characterize the mounds of both levels, pointing to a hydrothermal origin. Therefore, these structures are here called as hot springs. These were originated subaerially, on the margins of a closing epeiric sea developed on a large intracontinental sag basin. Hydrothermal fluids were sourced from deep circulating basin waters that erupted through intraplate deep-rooted faults. Our data suggests that these hot springs were active during distinct cycles of base level variations. Strata-confined silicification was enhanced during periods of high evaporation and hydrothermal exudation. Finally, the vertical and lateral facies associations of the Permian hot spring succession are compared with modern sites, and implications for the recognition of syn-depositional hydrothermally precipitated silica in ancient sedimentary basins are discussed.
Keywords: Epeiric sea; Hot springs; Hydrothermal fluids; Intraplate tectonics; Paraná Basin; Soft-sediment deformation structures; Teresina Formation